(untitled) (Scientific journal of the Fergana State University, 2023)
Thisarticle contains comments on the linguistic study of Navoi’s creativity. Including Navoi’s last epic "Khamsa" "Saddi Iskandariy", the fact that the poet as a poet wrote his works in Turkic and Persian languages, Persian-Tajik words used in the work, their grouping according to the semantic field, a dictionary of meanings, Farsi-Tajik synonyms and antonyms, the use of superlatives, the activity of Arabic and Persian words in the use of superlatives. Opinions were also expressed on the use of conjunctions, pronouns and repetitions used in the works of Navoi.